A Metal–Organic‐Framework‐Based Electrolyte with Nanowetted Interfaces for High‐Energy‐Density Solid‐State Lithium Battery. Issue 2 (27th November 2017) - Wang, Ziqi; Tan, Rui; Wang, Hongbin; Yang, Luyi; Hu, Jiangtao; Chen, Haibiao; Pan, Feng
Abstract: Solid‐state batteries (SSBs) are promising for safer energy storage, but their active loading and energy density have been limited by large interfacial impedance caused by the poor Li + transport kinetics between the solid‐state electrolyte and the electrode materials. To address the interfacial issue and achieve higher energy density, herein, a novel solid‐like electrolyte (SLE) based on ionic‐liquid‐impregnated metal–organic framework nanocrystals (Li‐IL@MOF) is reported, which demonstrates excellent electrochemical properties, including a high room‐temperature ionic conductivity of 3.0 × 10 ‐4 S cm ‐1, an improved Li + transference number of 0.36, and good compatibilities against both Li metal and active electrodes with low interfacial resistances. The Li‐IL@MOF SLE is further integrated into a rechargeable Li|LiFePO4 SSB with an unprecedented active loading of 25 mg cm ‐2, and the battery exhibits remarkable performance over a wide temperature range from −20 up to 150 °C. Besides the intrinsically high ionic conductivity of Li‐IL@MOF, the unique interfacial contact between the SLE and the active electrodes owing to an interfacial wettability effect of the nanoconfined Li‐IL guests, which creates an effective 3D Li + conductive network throughout the whole battery, is considered to be the key factor for the excellent performance of the SSB. Abstract : A novel solid‐like electrolyte featuring a high ionic conductivity with nanowetted interfaces and good Li‐metal compatibility is created by impregnating a Li + ‐containing ionic liquid into a metal–organic framework host. On this basis, the Li|LiFePO4 solid‐state battery with an unprecedented areal active loading exhibits good capacity retention over a wide temperature range.